Amphiphysin is necessary for organization of the excitation–contraction coupling machinery of muscles, but not for synaptic vesicle endocytosis in Drosophila - Razzaq, Azam (Cold Spring Harbor Laboratory Press, 2001)
Amphiphysins 1 and 2 are enriched in the mammalian brain and are proposed to recruit dynamin to sites of endocytosis. Shorter amphiphysin 2 splice variants are also found ubiquitously, with an enrichment in skeletal muscle. At the Drosophila larval neuromuscular junction, amphiphysin is localized postsynaptically and amphiphysin mutants have no major defects in neurotransmission; they are also viable, but flightless. Like mammalian amphiphysin 2 in muscles, Drosophila amphiphysin does not bind clathrin, but can tubulate lipids and is localized on T-tubules. Amphiphysin mutants have a novel phenotype, a severely disorganized T-tubule/sarcoplasmic reticulum system. We therefore propose that muscle amphiphysin is not involved in clathrin-mediated endocytosis, but in the structural organization of the membrane-bound compartments of the excitation–contraction coupling machinery of muscles.